THE IMPLEMENTATION OF MODERATION BASED INSTRUCTIONAL IN TEACHING ENGLISH - Pelu, Hanafi (Uniqbu Journal of Social Sciences, 2022)
Moderation is vital in education because it can help foster democratic education. Indonesia’s educational system should explore including the concept of moderation, particularly in Islamic schools. This research intends to examine how moderation is implemented in an Islamic school. The purpose of this research is to examine the adoption of moderation-based instruction in the teaching of English at Islamic Senior High School. The study’s subjects are English instructors and learners of Islamic Senior High School in Makassar, South Sulawesi, Indonesia. The ethnographic research design was used in this study. Observation, interview, note-taking, and documentation were employed to English teachers to explore the implementation of moderation-based instruction in English language teaching. This study found that English teachers always consider a modification in formulating learning indicators and objectives in the moderation-based instruction in teaching English. In formulating the learning indicators and objectives, teachers are always fair, do not take sides with one or a group of students, are adjusted to conditions that are suitable for students and the school environment and facilities, are not excessive, and always stay away from goals that can lead to violence. This study is expected to contribute to professional knowledge about how to adopt moderation in English language instruction in Islamic schools in Indonesia, as well as provide insights for policymakers and help improve the quality of English language instruction at the secondary school level